Comparison between age-predicted and measured maximal heart rate in professional soccer athletes - Garlipp, D. C.; Siqueira, O. D.; Crescente, L. A. B.; Jaeger, D. B.; Leiria, T. L. L. (International Journal of Sports Science, 2016)
The aim of this study was to compare the measure maximal heart rate (measure-HRmax) available in maximum treadmill test with age-predicted-HRmax from the Karvonen (Fox-HRmax), Tanaka (Tanaka- HRmax) and Nikolaidis (Nikolaids-HRmax) methods. Ninety players, aged 16 and 33 years, a first division club of Brazilian football participate in this study. A Bruce protocol was used in the treadmill to assess the maximal aerobic running speed. Measured-HRmax was defined as the highest value attained during the test. Data were expressed as mean, standard deviation (SD) of the mean, minimum and maximal values. Independent Student`s t-test, Bland-Altman analysis and Pearson`s correlation coefficient was using in statistical analyses. Our results showed that none of the three available equations (Fox, Tanaka and Nikolaids) provides accurate values of HRmax in a sample of professional soccer players. The three equations overestimated measure-HRmax. However, the equation that provided the most accurate measured-HRmax was the Nikolaids equation. This is true probably to the fact that this equation has been developed from a sample soccer player.